Does the economic integration of China affect growth and inflation in industrial countries? - Christian Dreger; Yanqun Zhang (FIW - Research Centre International Economics, 2013)
The Chinese economic development affects GDP growth and inflation in the advanced countries. A GVAR approach is used to model the interdependencies between the business cycles in China and industrial countries, including the US, the euro area and Japan. For robustness, the results are compared to those obtained by leading structural econometric models, such as NiGEM and OEF. Evidence is based on the responses to a Chinese shock stemming from the recent fiscal stimulus package. The results indicate that the impact on GDP growth in the advanced economies is substantial for the Asian region. The expansionary effects to the US and the euro area responses are much lower and decrease due to rising inflation pressure. The analysis also reveals that China is still highly vulnerable to shocks in industrial countries, including the government debt crisis in the euro area.
Keywords: E32; F15; C51; 330; GVAR; Chinese integration; shock transmission; euro area debt crisis